SOSIALISASI PENCEGAHAN DAN SENAM REMATIK PADA LANSIA DI POSYANDU LANSIA KASIH IBU KELURAHAN TANGKERANG LABUAI - Susanti, Nurvi; Rasyid, Zulmeliza; Harnani, Yessi; Nurlisis, Nurlisis; Hasrianto, Nofri (LPPM Institut Pendidikan Nusantara Global, 2023)
Rheumatism is a disease that attacks the joints and bones or supporting tissues around the joints, this class of diseases is an autoimmune disease that many elderly people suffer from. The initial survey was conducted in Tangkerang Selatan Village, Pekanbaru City, out of 8 elderly people, mostly 5 people with complaints such as body fatigue, difficulty moving, leg pain when walking, aches and pains, and stiffness that occur consistently. One of the efforts made by doing prevention and rheumatic exercises regularly is to reduce the pain from rheumatism. The purpose of this community service is to increase the knowledge of the elderly about health, namely by doing rheumatic prevention and exercises. The media is used for counseling leaflets and practicing rheumatic gymnastics movements. The method used is by giving post-tests and pret-tests. The results of this activity obtained elderly knowledge at the time of the Pret Test as much as 40% had poor knowledge and increased during the post-test by 70% with good knowledge. It is hoped that increasing knowledge and doing rheumatic gymnastics movements at the integrated service post and at home can prevent or reduce rheumatic symptoms in the elderly.